The Use of Herbal Medicines for Allergic Rhinitis - Prisya Dhiba Ramadhani (Eureka Herba Indonesia, 2022)
Allergic rhinitis (AR) is an immunoglobulin E–mediated illness that causes inflammation of the nasal mucosa. In recent years, the global incidence and prevalence of AR has been increased. AR has been treated with antihistamines, intranasal corticosteroids, decongestants, intranasal anticholinergics, intranasal cromolyn, leukotriene receptor antagonists, and immunotherapy. However, because many of the present medicines have documented negative side effects, there is a need to look for more effective and safer alternatives. Herbal therapy has long been used to treat the symptoms of AR, but its usefulness and safety have not been validated scientifically. In this review, recent research on the use of herbal medicine as a treatment for allergic rhinitis is collated and critically analyzed. From 2016 to 2021, the data was gathered mostly from English language publications published in journals or research from Pubmed databases. "Herbal medication" and "Allergic Rhinitis" were the terms or keywords used to discover relevant studies. This literature study may be useful in determining the potential utility of herbal medicine as a treatment for allergic rhinitis, determining the underlying mechanisms of action, and identifying natural product candidates for the development of innovative anti-allergic rhinitis drugs in the future.